Analysis of Factors Affecting Poverty Levels in Eastern Aceh District - Alfian; Iskandar Budiman; Haris Munandar (Fakultas Ekonomi dan Bisnis Islam, 2024)
Creating a more decent life in realizing prosperity for the Indonesian people is one of the goals of national development. However, the level of poverty is a serious problem in achieving a level of prosperity in Indonesia. This research aims to determine the influence of economic growth, unemployment, education, human development index, labor force participation level on poverty in East Aceh Regency. The research method used is quantitative research, the data used is secondary data. The research results show that the coefficient value for the economic growth variable is positive at 0.3334. The coefficient value for the unemployment variable is negative at (-0.0913). The coefficient value for the education variable is positive at 0.1722. The coefficient value for the human development index variable is negative at (-0.7112). The coefficient value for the labor force participation rate variable is positive at 0.02021.